Menanamkan Pendidikan Kewarganegaraan pada Siswa Madrasah - Sanjaya, Erwan; Fadhilla, Muhammad Dzaki; Harahap, Muhammad Nasir Husein; Rambe, Rahmansyah Fadlul (MASALIQ, 2023)
This study examines the inculcation of civic education among madrasa students. This type of research is qualitative research that describes data using a series of sentences. The method used in this study is descriptive. Descriptive methods are methods where the data source is words, images and data from books, journals and other scientific works. Furthermore, whatever is collected is likely to be the key to what is sought. Therefore, the use of this method does not produce numeric data, but rather descriptive data. This study used written data from scientific journals and previous research. Citizenship education is not just an ordinary lesson, because through civic education, new generations are created to love the homeland and forge a personality that is consistent with the national identity. The implementation of Pancasila values includes learning activities in religion, citizenship and other subjects, including teaching and instilling the precepts of Pancasila and implementing them in school activities. Instilling and applying Pancasila values in social life is very necessary because of how applying Pancasila values will affect people's thinking and Pancasila is really the foundation of the country. how. It is not the result of the thoughts of other people or of other peoples, but Pancasila is purely from the perspective of the soul, the ideology of its own people, specifically the Indonesian people. Regarding the learning outcomes of civics, educators should not always focus on teaching knowledge to students, but educators should also develop ethical values that match suitable for Pancasila. Interpersonal intelligence is one of the things that teachers can develop.